Farm Households in Egypt: A typology of vulnerability to climate change - Nin-Pratt, Alejandro; ElDidi, Hagar; Breisinger, Clemens; Kassim, Yumna (2019)
As part of the IFPRI Egypt Seminar in partnership with the American University in Cairo: “Climate-Smart Agriculture Solutions for Egypt”